Computational kinematics Proceedings of the 5th International Workshop on Computational Kinematics - Kecskeméthy, Andrés. (Springer Berlin Heidelberg :, 2009)
Computational kinematics is an enthralling area of science with a rich spectrum of problems at the junction of mechanics, robotics, computer science, mathematics, and computer graphics. The present book collects up-to-date methods as presented during the Fifth International Workshop on Computational Kinematics (CK2009) held at the University of Duisburg-Essen, Germany. The covered topics include design and optimization of cable-driven robots, analysis of parallel manipulators, motion planning, numerical methods for mechanism calibration and optimization, geometric approaches to mechanism analysis and design, synthesis of mechanisms, kinematical issues in biomechanics, balancing and construction of novel mechanical devices, detection and treatment of singularities, as well as computational methods for gear design. The results should be of interest for practicing and research engineers as well as Ph.D. students from the fields of mechanical and electrical engineering, computer science, and computer graphics. Indexed in Conference Proceedings Citation Index- Science (CPCI-S). Cable-Driven Parallel Manipulators -- Kinematic analysis of a spatial four-wire driven parallel crane without constraining mechanism -- Extension of Antipodal Theorem to Workspace Analysis of Planar Wire-Actuated Manipulators -- Modelling and Simulation of a Cable-Based Parallel Manipulator as an Assisting Device -- Closed-form Force Distribution for Parallel Wire Robots -- Parallel Manipulators (1) -- Computing the Configuration Space for Motion Planning between Assembly Modes -- Kinematic analysis of a class of analytic planar 3-RPR parallel manipulators -- Non-singular assembly mode change in 3-RPR-parallel manipulators -- Kinetostatic and Singularity Analyses of the 3- UPU Translational Parallel Robot -- Parallel Manipulators (2) -- Forward displacement analysis of a 3-RPR planar parallel manipulator revisited -- Sensitivity and Dexterity Comparison of 3-RRR planar parallel manipulators -- Inverse Kinematics and Motion Simulation of a 2-DOF Parallel Manipulator with 3-PUP Legs -- ON NEW CLASS OF PARALLEL-CROSS MECHANISMS -- Motion Planning -- Motion Interpolation with Bennett Biarcs -- Motion Estimation using a Statistical Solid Dynamic Method -- Spatial Generalization of the Planar Path Generation Problem -- Motion Planning of Nonholonomic Systems with Dynamics -- Numerical Methods -- Optimal Kinematic Calibration of Robots Based on Maximum Positioning-Error Estimation (Theory and Application to a Parallel-Mechanism Pipe Bender) -- Fast Distance Computation Using Quadratically Supported Surfaces -- On the Computation of the Home Posture of the McGill SchÃ÷nflies-Motion Generator -- Hardware-in-the-Loop Simulation of Constraint Elements in Mechanical Systems -- Geometrical Methods -- Explicit Algebraic Solution of Geometrically Simple Serial Manipulators -- 3R Wrist Positioning - a Classical Problem and its Geometric Background -- A Geometric Newton-Raphson Method for Gough-Stewart Platforms -- Aspects of Clifford Algebra for Screw Theory -- Synthe